Nano-porous structures via self-assembly of amphiphilic triblock copolymers: influence of solvent and molecular weight. Issue 2 (11th December 2017) - Nehache, S.; Semsarilar, M.; Deratani, A.; In, M.; Dieudonné-George, P.; Lai Kee Him, J.; Bron, P.; Quémener, D.
Abstract : Self-assembly of ABA triblock copolymer micelles into porous materials which are subsequently used as filtration membranes. Abstract : Control of film structures made from a polystyrene-polystyrene sodium sulfonate-polystyrene (PS-PNaSS-PS) copolymer micellar solution is investigated in a THF/water mixture. Four different copolymers (varying molecular weights) are synthesised via RAFT (Reversible Addition Fragmentation chain Transfer) polymerisation. Depending on parameters such as copolymer molecular weight, solvent composition and copolymer concentration, the PS-PNaSS-PS triblock self-assembles into different morphologies in solution and dry state. The effect of each parameter is investigated using characterization techniques such as AFM, TEM, Cryo-TEM, SEM and SAXS. The morphologies obtained for PS-PNaSS-PS are found to be extremely sensitive when the water content of the micellar solution is low. Among the structures observed, a highly ordered nano-porous film is obtained using a PS10k -PNaSS6k -PS10k triblock copolymer solution containing 3.0 wt% of water. This micellar solution is used to prepare a porous membrane for filtration applications. Pure water filtration data suggest a pore size in the range of ultrafiltration, making these membranes attractive for applications in the food industry, for bacteria, virus and protein removal.